Land, memory, reconstruction, and justice : perspectives on land claims in South Africa - Walker, Cherryl (Athens, Ohio : Ohio University Press, 2010)
""An outstanding and timely collection, Land, Memory, Reconstruction , and Justice is the most comprehensive treatment of land restitution i n South Africa. It brings together a wealth of thematic and case study material from across the country and provides a rounded view of the mul tiple meanings of land restitution in postapartheid South Africa."---Be n Cousins, Institute for Poverty, Land and Agrarian Studies (PLAAS), Un iversity of the Western Cape" ""Written and edited by some of the leadi ng scholars and activists on the land question in South Africa, this bo ok is set to make an important and welcome contribution."---Lungisile N tsebeza, University of Cape Town" "Land is a significant and controvers ial topic in South Africa. Addressing the land claims of those disposse ssed in the past has proved to be a demanding, multidimensional process . In many respects the land restitution program that was launched as pa rt of the county's transition to democracy in 1994 has failed to meet e xpectations, with ordinary citizens, policymakers, and analysts questio ning not only its progress but also its outcomes and parameters." "Land , Memory, Reconstruction, and Justice brings together a wealth of topic al material and case studies by leading experts in the field who presen t a rich mix of perspectives from politics, sociology, geography, socia l anthropology, law, history, and agricultural economics. The collectio n addresses both the material and the symbolic dimensions of land claim s, in rural and urban contexts, and explores the complex intersection o f issues confronting the restitution program, from the promotion of liv elihoods to questions of rights, identity, and transitional justice."-- BOOK JACKET.
Reconciling the past, present, and future : the parameters and pract ices of land restitution in South Africa / Ruth Hall -- Giving la nd back or righting wrongs? Comparative issues in the study of land res titution / Derick Fay and Deborah James -- Change through jurispr udence : the role of the courts in broadening the scope of restitution / Hanri Mostert -- Urban restitution narratives : Black River, Ca pe Town / Uma Dhupelia-Mesthrie -- Right to land restitution as i nspiration for mobilization / Marc Wegerif -- Choosing cash over land in Kalk Bay and Knysna : the time factor in urban land claims / Anna Bohlin -- Securing postsettlement support toward sustainabl e restitution : lessons from Covie / Angela Conway and Tim Xipu -- Acrimonious stakeholder politics ; reconciliation and redevelopment in District Six / Christiaan Beyers -- "Model tribes" and iconic conservationists? Tracking the Makuleke restitution case in Kruger Nat ional Park / Steven Robins and Kees van der Waal -- Khomani San l and claim against the Kalahari Gemsbok National Park : requiring and ac quiring authenticity / Christ de Wet and Eric Mgujulwa -- Land re stitution and community politics : the case of Roosboom in KwaZulu-Nata l / Chizuko Sato -- Land claims and comanagement of protected are as in South Africa : exploring the challenges / Thembela Kepe -- Restitution in default : land claims and the redevelopment of Cato Mano r, Durban / Cherryl Walker -- Unfinished business : the role of g overnmental institutions after restitution of land rights / Alan Dod son -- Restitution, agriculture, and livelihoods : national debates and case studies from Limpopo Province / Michael Aliber ... [et. al. ] -- Strategic questions about strategic partners : challenges and p itfalls in South Africa's new model of land restitution / Bill Derma n, Edward Lahiff, and Espen Sjaastad.
Includes bibliographical references and index
Keywords: Land reform -- South Africa; Land reform -- Social aspects -- South Africa; Land tenure -- South Africa; Restitution